Experiencing the continuing training of Higher Education Chemistry teachers (Práxis Educativa, 2024)
Higher Education professors who work with specific knowledge of the Natural Sciences have little access to theories and knowledge related to didactics, which has led to greater attention being paid to continuing education. Thus, in this work, the potential of a continuing education project developed in the participants’ work environment is analyzed, in a partnership between professors from the field of Chemistry and the field of Chemical Education. In this project, professors came into contact with studies in the field of Education and planned lessons based on these studies, developing them in their own classes. As a result, participants highlighted students’ good receptivity and active participation and identified factors that helped in the learning process. With that, it is argued that the most direct connection between theory and practice occurred through the partnership between Chemists and Chemistry Educators and through the training in the professors’ work environment.Keywords: Continuing training of professors. Higher Education. Chemistry.